Реформування системи місцевих органів виконавчої влади та органів місцевого самоврядування: сьогодення та перспективи - Бабич, О.М. (Часопис Київського університету права, 2009)
Статья посвящена проблемам реформирования системы местных органов исполнительной власти и органов местного самоуправления в Украине, его правовым аспектам. Автор раскрывает основные составляющие процесса нормативно-правового обеспечения децентрализации исполнительной власти в Украине и рассматривает обуславливающие его факторы. Уделено внимание существующим проблемам правового сопровождения процесса реформирования, несогласованности действий ответственных за этот процесс центральных органов исполнительной власти Украины. The article is devoted to the problems of reforming the bodies of local executive power as well as local administrations and their legal aspects in Ukraine. The author has exposed the main components of regulation and legal provision of decentralizing of the executive power in Ukraine and considers the factors that ensure it. Attention is paid to present problems of the reforming process legal provision lack of coordinated actions from responsible for this process central bodies of executive power.